Exercise and heat stress: performance, fatigue and exhaustion - a hot topic - Schlader, Z. J.; Stannard, S. R.; Mündel, T. (British Journal of Sports Medicine, 2011)
This editorial proposes that the theories of anticipatory regulation and avoidance and the critical core temperature are "safety" mechanisms synergistically maintaining thermoregulation, and therefore homeostasis, during "real-world" exercise in the heat. These thermoregulatory mechanisms are suggested to prevent the onset of exertional heat stroke.